Розробка компонентів інформаційної системи нагадувань, розкладів та списків справ - Клішов, М. Р. (ХНУРЕ, 2024)
This project is dedicated to the creation of a web system, where users can make their remainders. There are three categories for reminders: specific date, intervals and schedule of tasks. The schedule of tasks can be created both by hours per day and by days per week. The user can receive reminders from each category: to the desired messenger via a chat bot, to e-mail and via a browser directly. All necessary information is entered into the system on the website of the application and retain in the database. User interaction with an application is possible through a website on the Internet and specific chat bots.
Keywords: система нагадувань; управління розкладами; база даних справ; інтеграція з календарем